[OP.7C.04] ARTERIAL STIFFNESS IS INDEPENDENTLY CORRELATED WITH MYOCARDIAL MECHANOENERGETIC EFFICIENCY IN A GENERAL POPULATION IN NORTHERN ITALY: THE VOBARNO STUDY. (September 2017) - Paini, A.; Salvetti, M.; Stassaldi, D.; Bertacchini, F.; Maruelli, G.; Rubagotti, G.; Favro, S.; Riviera, M.; Dallapellegrina, L.; Moretti, M.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: A non-invasive approach for the estimation of mechanical efficiency through the calculation of the ratio between stroke work and HR–pressure product has been recently proposed by de Simone et al. This index, which expresses the amount of blood pumped in a single beat in 1 second by the heart, may be easily obtained by echocardiography. The aim of our study was to evaluate the determinants of myocardial mechanoenergetic efficiency index (MEEi), calculated as as stroke volume/heart rate and indexed to LV mass (MEEi = MEE/LVM) in a large general population sample in Northern Italy. Design and method: We evaluated 478 subjects participating in a general population study in Northern Italy (Studio Vobarno). All subjects underwent a physical examination with measurement of clinic blood pressure (BP). In all subjects laboratory examinations, 24 hours blood pressure measurement, echocardiography, and assessment of carotid-femoral pulse wave velocity (PWV) were performed. Results: Subjects had a mean age of 58 ± 10 years, a BMI of 26 ± 4, 44% were males, 69% had arterial hypertension (55% treated). MEEi was lower in males and in patients with increased PWV. MEEi was inversely correlated with age, BMI, waist circumference, clinic and 24 hours BP, glucose, uric acid, triglycerides and directly correlated with HDL. MEEI was also inversely correlated with relative wall thickness (RWT) and PWV. At linear regression multivariate (?) analysis MEEi remained independently related to male gender (β = 0.16, p < 0.001), BMI (β = −0.13, p < 0.005), RWT (β = −0.56, p < 0.001) and PWV (β = −0.10, p < 0.05). Conclusions: In a large sample of general population in Northern Italy myocardial mechanoenergetic efficiency was inversely correlated with arterial stiffness, independently of multiple possible confounders.